Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\Leftrightarrow\left|x-1\right|=3-2x\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(2x-3-x+1\right)\left(2x+3+x-1\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}\left(x-2\right)\left(3x+2\right)=0\\x< =\dfrac{3}{2}\end{matrix}\right.\)
=>x=-2/3
b: Trường hợp 1: x<-3
Pt sẽ là:
\(-x-1-x-3=10-4x\)
=>-2x-4=10-4x
=>2x=14
hay x=7(loại)
Trường hợp 2: -3<=x<-1
Pt sẽ là \(x+3-x-1=10-4x\)
=>10-4x=2
=>4x=8
hay x=2(loại)
Trường hợp 3: x>=-1
Pt sẽ là x+1+x+3=10-4x
=>2x+4=10-4x
=>6x=6
hay x=1(nhận)
\(a,\left(\frac{3}{8}+-\frac{3}{4}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\left(-\frac{3}{8}+\frac{7}{12}\right):\frac{5}{6}+\frac{1}{2}\)
= \(\frac{5}{24}:\frac{5}{6}+\frac{1}{2}\)
= \(\frac{1}{4}+\frac{1}{2}\)
= \(\frac{3}{4}\)
b)\(-\frac{7}{3}.\frac{5}{9}+\frac{4}{9}.\left(-\frac{3}{7}\right)+\frac{17}{7}\)
=\(-\frac{35}{27}+\left(-\frac{4}{21}\right)+\frac{17}{7}\)
= \(-\frac{35}{27}+\frac{47}{21}\)
= \(\frac{178}{189}\)
c) \(\frac{117}{13}-\left(\frac{2}{5}+\frac{57}{13}\right)\)
= \(\frac{117}{13}-\frac{311}{65}\)
= \(\frac{274}{65}\)
d) \(\frac{2}{3}-0,25:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{4}:\frac{3}{4}+\frac{5}{8}.4\)
= \(\frac{2}{3}-\frac{1}{3}+\frac{5}{2}\)
= \(\frac{1}{3}+\frac{5}{2}\)
= \(\frac{17}{6}\)
a) \(13-3\left|x+5\right|=4\)
\(\Leftrightarrow3\left|x+5\right|=9\)
\(\Leftrightarrow\left|x+5\right|=3\)
\(\Leftrightarrow\orbr{\begin{cases}x+5=3\\x+5=-3\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-2\\x=-8\end{cases}}\)
b) \(x-\frac{3}{4}=2x+\frac{1}{2}\)
\(\Leftrightarrow x-2x=\frac{1}{2}+\frac{3}{4}\)
\(\Leftrightarrow-x=\frac{5}{4}\)
\(\Leftrightarrow x=\frac{-5}{4}\)
c) ĐKXĐ : x khác -3
\(\frac{x+1}{x+3}=\frac{1}{5}\)
\(\Leftrightarrow5\left(x+1\right)=x+3\)
\(\Leftrightarrow5x+5=x+3\)
\(\Leftrightarrow5x-x=-5+3\)
\(\Leftrightarrow4x=-2\Leftrightarrow x=\frac{-1}{2}\)
a) 13 - 3|x + 5| = 4
=> 3|x + 5| = 9
=> |x + 5| = 3
=> x + 5 = 3 hoặc x + 5 = -3
=> x = -2 hoặc x = -8
b) \(\frac{x-3}{4}=\frac{2x+1}{2}\)
=> 2(x - 3) = 4(2x + 1)
=> 2x - 6 = 8x + 4
=> 2x - 6 - 8x - 4 = 0
=> -6x - 10 = 0
=> -6x = 10
=> x = 10/-6 = -10/6 = -5/3
c) \(\frac{x+1}{x+3}=\frac{1}{5}\)
=> 5(x + 1) = x + 3
=> 5x + 5 - x - 3 = 0
=> 4x + 2 = 0
=> 4x= -2 => x = -1/2